Pelatihan Kecap Sehat Saccharum Officinarum Desa Rantau Alih Kecamatan Sukakarya - Julia Nur Fadilah; Indah Meilanda; Yusfan Imansyah; Fitria Lestari (Pusat Penelitian Pengabdian Pada Masyarakat Sekolah Tinggi Ilmu Tarbiyah Al-Fattah Siman Lamongan, 2021)
This community service aims to increase the skills of Rantau Alih community’s by using local potentials of Rantau Alih village which is Saccharum Officinarum that processed into soy sauce.The methodologyof this activity consist of sosialiszation, training, and workshop. An evaluation held after the activity by the team to find out the Rantau Alih community’s participation and the understandings level concern of the healthy soy sauce. The result of this research shows that through the organoleptic test,the flavour tester, scents, form, and color of the product. In other ways, through the antimicrobial test, this product was able to be consumed and turned into superior product of Rantau Alih village. Based on the activity that have been carried out, however the follow up activityto keep the field monitoring at least once in a month and packaging assists also the product marketing, so it can be recognized by the large people.